2008
DOI: 10.1158/0008-5472.can-08-0763
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inhibition of ATM Kinase Is Sufficient to Enhance Cellular Sensitivity to Ionizing Radiation

Abstract: In response to DNA damage, the ATM protein kinase activates signal transduction pathways essential for coordinating cell cycle progression with DNA repair. In the human disease ataxia-telangiectasia, mutation of the ATM gene results in multiple cellular defects, including enhanced sensitivity to ionizing radiation (IR). This phenotype highlights ATM as a potential target for novel inhibitors that could be used to enhance tumor cell sensitivity to radiotherapy. A targeted compound library was screened for poten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(162 citation statements)
references
References 47 publications
8
154
0
Order By: Relevance
“…To that end, we tested the autophagy interfering capacity of two other compounds known to inhibit ATM kinase, i.e. caffeine (27) and CP466722, a recently introduced highly specific and potent ATM inhibitor with a structure distinct from that of KU55933 (28). As analyzed by their ability to inhibit ionizing radiation (IR)-induced phosphorylation (Ser-15) and subsequent stabilization of a well-described ATM target, tumor protein 53 (TP53) in MCF7 cells, 4 mM caffeine and 5 M CP466722 were as effective in inhibiting ATM activity as 2 M KU55933 ( Fig.…”
Section: Identification Of Small Molecule Inhibitors Of Autophagy-mentioning
confidence: 99%
“…To that end, we tested the autophagy interfering capacity of two other compounds known to inhibit ATM kinase, i.e. caffeine (27) and CP466722, a recently introduced highly specific and potent ATM inhibitor with a structure distinct from that of KU55933 (28). As analyzed by their ability to inhibit ionizing radiation (IR)-induced phosphorylation (Ser-15) and subsequent stabilization of a well-described ATM target, tumor protein 53 (TP53) in MCF7 cells, 4 mM caffeine and 5 M CP466722 were as effective in inhibiting ATM activity as 2 M KU55933 ( Fig.…”
Section: Identification Of Small Molecule Inhibitors Of Autophagy-mentioning
confidence: 99%
“…To date, three selective inhibitors of ATM kinase activity have been identified: KU55933, 16 CP466722, 17 and KU60019. 18 As expected, ATM kinase inhibition using KU55933, CP466722 or KU60019 is sufficient to enhance cellular sensitivity to IR.…”
Section: Atm Kinase Inhibitorsmentioning
confidence: 99%
“…18 As expected, ATM kinase inhibition using KU55933, CP466722 or KU60019 is sufficient to enhance cellular sensitivity to IR. [16][17][18] We showed that the competitive ATP inhibitors KU55933 and KU60019 can be used as "molecular switches" to selectively and transiently inhibit ATM kinase activity in cells. ATM kinase activity is inhibited in irradiated cells within 15 min of the addition of KU55933 or KU60019 and is restored within 15 min following the removal of either inhibitor.…”
Section: Atm Kinase Inhibitorsmentioning
confidence: 99%
“…It is well established that ATM is essential in maintaining G 2 checkpoint function (Terzoudi et al, 2005;Deckbar et al, 2007) through inhibition of cyclin B1/cdc2 (Abraham, 2001). We, therefore, examined the effect of a specific and potent ATM inhibitor, KU55933 (Rainey et al, 2008), which is known as a 'molecular switch' because of its rapid and reversible inactivation of ATM (White et al, 2008), on centromeric instability. Being aware that ATM also has G 1 /S checkpoint functions (Abraham, 2001), we particularly designed experiments to examine the effect of KU55933 treatment without the confounding factor of G 1 /S checkpoint inactivation.…”
Section: Resultsmentioning
confidence: 99%